2022
DOI: 10.1371/journal.pone.0264471
|View full text |Cite
|
Sign up to set email alerts
|

Visual attention prediction improves performance of autonomous drone racing agents

Abstract: Humans race drones faster than neural networks trained for end-to-end autonomous flight. This may be related to the ability of human pilots to select task-relevant visual information effectively. This work investigates whether neural networks capable of imitating human eye gaze behavior and attention can improve neural networks’ performance for the challenging task of vision-based autonomous drone racing. We hypothesize that gaze-based attention prediction can be an efficient mechanism for visual information s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Loquercio et al [20] train DroNet with simulation data using domain randomization and also change the output layers to produce a velocity vector that drives the robot through the gate. Pfeiffer et al [22] combine DroNet with an attention map as an end-to-end network to capture visual-spatial information allowing the system to track high-speed trajectories. In this work, we compare PencilNet with two variants of DroNet: DroNet-1.0 with the full set of parameters as in [17], and DroNet-0.5 with only half of the filters as in [20].…”
Section: A Baseline Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Loquercio et al [20] train DroNet with simulation data using domain randomization and also change the output layers to produce a velocity vector that drives the robot through the gate. Pfeiffer et al [22] combine DroNet with an attention map as an end-to-end network to capture visual-spatial information allowing the system to track high-speed trajectories. In this work, we compare PencilNet with two variants of DroNet: DroNet-1.0 with the full set of parameters as in [17], and DroNet-0.5 with only half of the filters as in [20].…”
Section: A Baseline Methodsmentioning
confidence: 99%
“…The approach in [15] also segments the gates with U-Net but associates the gate corners differently by combining corner pixel searching and re-projection error rejection. Recently, end-to-end methods [20]- [22] using a single DNN that outputs tracking targets for controllers are considered to reduce the latency introduced by traditional modulation of perception, planning, and control sub-problems. In both lines of work, the quality of a gate perception, either through explicit mapping of gates or implicit feature-based understanding, dictates the performance of the system overall.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, eliminating inertial information might have some engineering advantages too, e.g., data throughput, power consumption, and lower cost. Seminal works in this direction try to understand how humans solve this task [6], [171]. They found that expert pilots can control drones despite a 200ms latency, which is compensated by the human brain.…”
Section: B Challenge 2: Flying From Purely Visionmentioning
confidence: 99%
“…The robotics and perception (RPG) and autonomous system lab (ASL) teams at the University of Zürich (UZH) both focus on the improvement of navigation methods for visual perception (Pfeiffer et al, 2022). They make Agilicious an open‐source framework for quadrotor drones (Foehn et al, 2022).…”
Section: Drone Localization In Underground Structuresmentioning
confidence: 99%